SIMULATION OF DRAINAGE DISPOSER (1981)
PURPOSE:To obtain a highly accurate reference index value, by adopting an unsteady model which takes into consideration a big quality variation of a drainage flowing into a drainage disposing plan, as a mathematic model for an aeration vessel in case where a simulation is performed. CONSTITUTION:An in-flow amount of a drainage is divided to a plurality of ranges. An individual mixing model is set correspondingly to each mode representing a divided different drainage amount. These mixing models are combined chronologically to form an unsteady model which is used as a mathematic model for an aeration vessel. As a basic mixing model is used a model which is obtained by combining a single stage complete mixing model (in case where a number of stages is considered as one in a vessel series model) and a liquid extruding model (in case where a number of stages is considered as infinite) with a weight coefficient. Owing to the usage of such an unsteady model for offering chronological qualities of an in-flowing drainage and a returning sludge and also chronological data of an aeration air amount, the time series data of BOD, SS and DO can be generated at a high accuracy.